The Analysis of Factors Affecting Honorer Employees Financial Satisfaction in Politeknik Negeri Medan - Yulifati Laoli; Supaino Supaino; Khairul Khairul; Jantianus Jantianus; Darwin S.H. Damanik (Syntax Corporation Indonesia, 2022)
This This study aims to determine and analyze the effect of Financial Knowledge, Income, and Financial Behavior on financial satisfaction. This research was conducted by distributing questionnaires to 54 employees of the Class IB Binjai District Court. The sampling technique used the simple random sampling method. The research method used is multiple linear regression analysis. The results of the research simultaneously show that Financial Knowledge, Income, and Financial Behavior have a significant effect on the Financial Satisfaction of the employees of the Class IB Binjai District Court. Partially it shows that Financial Knowledge, Income, and Financial Behavior have a positive and significant effect on financial satisfaction for Class IB Binjai District Court employees.